The Effect of Easy Access to Mobile Banking, Financial Literacy, and Social Environment on Student Non-Cash Transactions - Syamsulrizal Syamsulrizal; Rosmida Rosmida (Universitas KH. Abdul Chalim Mojokerto, 2025)
The digitalization of the payment system in Indonesia is growing rapidly, but the use of non-cash transactions among students is still not optimal even though access to mobile banking is getting easier, thus showing a gap between the availability of technology and user behavior. This study aims to analyze the influence of ease of access to mobile banking, financial literacy, and social environment on non-cash transactions in students of the Public Finance Accounting Study Program, Bengkalis State Polytechnic. The method used was a quantitative approach with SEM-PLS, and data was obtained through the distribution of questionnaires to 230 students who were active users of mobile banking. All research indicators were declared valid with an outer loading value of 0.626–0.892 and AVE above 0.50, and reliable with a Composite Reliability of 0.893–0.925. The results showed that the ease of access to mobile banking had a significant effect on non-cash transactions (coefficient 0.437; p < 0.001), financial literacy also had a significant effect (coefficient 0.350; p < 0.001), while the social environment did not have a significant effect (coefficient 0.079; p = 0.113). An R² value of 0.599 indicates that the three variables are free to explain 59.9% of non-cash transaction variations, with a Q² value of 0.604 indicating the model's strong predictive capabilities. These findings confirm that technology factors and financial understanding are the main determinants of student non-cash transaction behavior, while social influences do not play a strong role. Therefore, it is recommended that educational institutions strengthen digital financial literacy and work with banks to improve education on digital financial services to encourage the use of non-cash transactions more optimally.